Domains of Everyday Creativity and Personal Values - Lebedeva, Nadezdha; Schwartz, Shalom H.; Van De Vijver, Fons J. R.; Plucker, Jonathan; Bushina, Ekaterina (Frontiers in Psychology, 2019)
We examined the applicability of the hybrid model of creativity, which specifies distinct domains that all express an underlying general creativity factor, in data from representative samples from Central Russia and the North Caucasus (N = 2,046). Using multigroup confirmatory analysis, Study 1 supported the invariance of a model with the six unifactorial domains (i.e., crafts, visual arts, performance, theater, products for work, and machine graphics) at the first level and a general creativity factor at the second level. Study 2 examined socio-demographic characteristics and 19 basic values that might be associated with creative activity. The more modern Central Russian region scored higher on global creativity and on all 6 domains. Of the 4 higher order values in the Schwartz model, Openness to Change values correlated positively and Conservation values correlated negatively with global creativity and with creativity in most domains. Variation across domains in the specific values that predicted creativity revealed that creativity in each domain had some unique motivators. We draw on culture and social structure to explain differences between regions in the value motivators of creativity.